Aloperin improves liver non-alcoholic steatohepatitis in vitro and in vivo - Zhongsheng Guo; Ruyu Liu; Liwei Guo; Sumei Lu; Min Yang; Shaofei Wu; Yong An (Archives of Medical Science)
Introduction The aim of this work is to investigate the inhibitory effect of aloperin (Alo) on hepatocyte apoptosis in non-alcoholic fatty liver disease, and the underlying mechanism.